2021
DOI: 10.1111/and.14143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypothermia and pentoxifylline on the adnexal torsion/detorsion injuries in a rat testis model

Abstract: This study was designed to investigate the effects of separate and combined administration of hypothermia and pentoxifylline to preserve the effects on the testicles in an experimental model of testicular torsion/ detorsion injuries in rats. Forty male adult Wistar rats were randomly divided into five groups, control, torsion/detorsion (TD), torsion/detorsion/hypothermia (TD+ICE), torsion/detorsion received of pentoxifylline (40mg/kg, ip) (TD+PTX) and torsion/detorsion/hypothermia/PTX (TD+ICE+PTX). Left testic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Results of our current study also confirmed that literature information and we observed significantly suppression of Bcl-2 expression in I/R exposed testis. Furthermore, targeting vascular dilation in ischemic organs up-regulates anti-apoptotic Bcl-2 expression, which is probably a result of re-oxygenation as fast as possible (Elmimehr et al, 2021). Despite the apoptotic regulators, cellular NF-κB is suspected to be responsible for the regulation of testicular I/R injury and results of previous experiments reported antioxidant substances inhibit Caspase 3 expression through NF-κB signalling (Afolabi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Results of our current study also confirmed that literature information and we observed significantly suppression of Bcl-2 expression in I/R exposed testis. Furthermore, targeting vascular dilation in ischemic organs up-regulates anti-apoptotic Bcl-2 expression, which is probably a result of re-oxygenation as fast as possible (Elmimehr et al, 2021). Despite the apoptotic regulators, cellular NF-κB is suspected to be responsible for the regulation of testicular I/R injury and results of previous experiments reported antioxidant substances inhibit Caspase 3 expression through NF-κB signalling (Afolabi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… [ 27 ] Rat model Suture 2 h Low midline laparotomy 30 days HBO 1 and 12 h post-ischeamia and once daily for 30 days 100 % oxygen for 1 h at the pressure of 2.4 atm for 30 days HBO ameliorated I/R-induced testicular toxicity by preventing oxidative stress, inflammatory response, and reducing NO formation [ 269 ] Rat model Clamp 4 h Inguinal incisions. 2 weeks HBO 150 min post-ischeamia and immediately after ischeamia 90 min treatment at 2.5 atm with 100 % oxygen HBO prevented I/R-induced testicular injury by preserving the germinal epithelium Hypothermia [ 270 ] Rat model Clamp 4 h Scrotum 1 h Hypothermia 5s, 10s intermittent reperfusion 4 0 c Hypothermia reversed I/R-induced ↓MDA, MPO [ 271 ] Rat model Suture 4 h Scrotum 4 h Pentoxifylline, Hypothermia 30 min pre detorsion 40 mg/kg Hypothermia reversed I/R-induced ↓aperm count and testosterone↓MDA↓Bcl 2, caspase 3 and Bax [ 272 ] Rat model Suture 2 h Scrotum 2 h Hypothermia And vit E 30 min, 90min and 30 min befor...…”
Section: Non-pharmacological Potentials In the Management Of I/r Injurymentioning
confidence: 99%
“…Nevertheless, there was no biochemical or histological advantage for hypothermia, intermittent reperfusion, or combination treatments. In another study, Elmimehr et al [ 271 ] reported the impacts of hypothermia and pentoxifylline on the adnexal torsion/detorsion injuries in a rat testis model. Pentoxifylline as an antioxidant component, raised the activities of antioxidant enzymes, decreased the expression of the BAX gene ( Bcl-2 Associated X-protein ) and dropped the rate of apoptosis in testicular tissues of rats after torsion detorsion, while hypothermia, and hypothermia plus pentoxifylline, did not manifest this.…”
Section: Non-pharmacological Potentials In the Management Of I/r Injurymentioning
confidence: 99%